1962
DOI: 10.1128/jb.84.1.130-136.1962
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Detection of Pleuropneumonia-Like Organisms in Cell Cultures by Fluorescent Antibody and Cultural Procedures

Abstract: B3ARILE, MICHAEL F. (National Institutes of Health, Bethesda, AMd.), WX ALTER F. iMALIZIA, AND DONALD B. RIGGS. Incidence and detection of pleuropneumonia-like organisms in cell cultures by fluorescent antibody and cultural procedures. J. Bacteriol. 84:130-136. 1962-A total of 102 tissue-cell cultures from 17 separate laboratories was examined for pleuropneumonia-like organisms (PPLO) by the fluorescent antibody and cultural procedures. PPLO were isolated from 48 of the 49 tissue-cell cultures found positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1964
1964
1978
1978

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The results of this investigation as well as those of Collier (1957), Corriell et al (1960) and Bailey et al (1961) establish that a large proportion of PPLO from tissue cultures are M. hominis type 1. Barile, Malizia & Riggs (1962), using a fluorescent antibody technique, found that 48 strains from tissue cultures were antigenically related, but did not identify the serotype. One of these, H.Ep2, proved in this present survey to be M. hominis type 1-further evidence of the widespread contamination of cell lines by this species.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this investigation as well as those of Collier (1957), Corriell et al (1960) and Bailey et al (1961) establish that a large proportion of PPLO from tissue cultures are M. hominis type 1. Barile, Malizia & Riggs (1962), using a fluorescent antibody technique, found that 48 strains from tissue cultures were antigenically related, but did not identify the serotype. One of these, H.Ep2, proved in this present survey to be M. hominis type 1-further evidence of the widespread contamination of cell lines by this species.…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma species was first reported by Robinson et al (14) and has since been found to be a relatively common occurrence (2,3,6,15). The effects of mycoplasmata contaminants in cell cultures are numerous and depend on the species involved and the type of cell infected.…”
Section: The Contamination Of Animal Cell Cultures Withmentioning
confidence: 99%
“…The indirect immunofluorescent technique (IIP) of Barile et al (1962) and Del Guidice et al 1967 Control slides were treated with normal horse serum or PBS in place of specific antiserum. All isolates of M. ovipneumoniae had "typical" colony morphology, i.e., centerless and lacy type colonies when grown on FA, while all other mycoplasmas isolated had "fried egg" type colony morphology (Figs 1 and 2).…”
Section: Indirect Xminunofluorescent Techniquementioning
confidence: 99%